A life on our planet : my witness statement and a vision for the future - Attenborough, David, 1926-; Hughes, Jonnie; Harper, Lizzie; Spetch, Meghan (London Witness books, 2020)
As a young man, Attenborough felt he was out there in the wild, experiencing the untouched natural world. But it was an illusion. The tragedy of our time has been happening all around us, barely noticeable from day to day: the loss of our planet's wild places, its biodiversity. Here he shares his witness statement from a lifetime of wisdom. And he offers a hopeful vision for the future: how we can work to restore the wonderful world we inherited. --
Introduction: Our greatest mistake -- My witness statement -- What lies ahead -- A vision for the future: how to rewild the world -- Conclusion: Our greatest opportunity.
Includes bibliographical references and index.
Keywords: Natural history; Biodiversity conservation; Pollution; Pollution; Biodiversity conservation; Natural history; Natural history; Biological diversity conservation